2023
DOI: 10.7717/peerj.15293
|View full text |Cite
|
Sign up to set email alerts
|

Selective HDAC6 inhibitor TubA offers neuroprotection after intracerebral hemorrhage via inhibiting neuronal apoptosis

Abstract: A large body of evidence has demonstrated that neuronal apoptosis is involved in the pathological process of secondary brain injury following intracerebral hemorrhage (ICH). Additionally, our previous studies determined that the inhibition of HDAC6 activity by tubacin or specific shRNA can attenuate neuronal apoptosis in an oxygen-glucose deprivation reperfusion model. However, whether the pharmacological inhibition of HDAC6-attenuated neuronal apoptosis in ICH remains unclear. In this study, we used hemin-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Compound 2 at 10 μM could produce a 17.76 % increase in cell survival, which showed potential neuroprotective activity (Figure 4C and Table S2 ). Previous studies have shown that cell apoptosis is one of the major events that hemin‐induced cell death [25] . So, we also double‐stained with Annexin V‐FITC and PI to analyze the percentage of apoptotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2 at 10 μM could produce a 17.76 % increase in cell survival, which showed potential neuroprotective activity (Figure 4C and Table S2 ). Previous studies have shown that cell apoptosis is one of the major events that hemin‐induced cell death [25] . So, we also double‐stained with Annexin V‐FITC and PI to analyze the percentage of apoptotic cells.…”
Section: Resultsmentioning
confidence: 99%